Cryopreservation of Seminiferous Tubules of Immature Rat Testes with Using of Low Cooling Rates - Yukhta, Mariia S.; Volkova, Nataliia O.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 185